An efficient Co-NC composite additive for enhancing interface performance of carbon-based perovskite solar cells. (20th October 2020) - Geng, Cong; Xie, Yahong; Wei, Peng; Liu, Haichao; Qiang, Yue; Zhang, Yi
Highlights: Co-NC composite prepared by ZIF-67 as sacrificial template. Hole transfer was enhanced by incorporating Co-NC(HCl) in carbon electrode. CCo-NC based hole-conductor-free PSC showed high efficiency and long-term stability. The mechanism of improved performance is discussed in detail. Abstract: Hole transporting material (HTM)-free carbon-based perovskite solar cells (C-PSCs) have been regarded as one of the most promising solar cell systems owing to their superior long-term stability and low cost. However, using commercial conductive carbon (CC) paste to prepare carbon electrode (CE) usually leads to a large number of defects at the perovskite/CE interface, often resulting in a low fill factor (FF) and poor photoelectric conversion efficiency (PCE). In this paper, by pyrolyzing ZIF-67 and etching with HCl, the Co-NC(HCl) composite with a large specific surface area are prepared. Combining this material with CC paste in different proportions, a series of HTM-free PSCs structured as FTO/SnO2 /perovskite/CE are fabricated. Our experimental results demonstrate that the incorporation of Co-NC(HCl) composite efficiently improves interface performance of perovskite/CE, suppresses charge recombination and promotes hole extraction, consequently enhancing the photovoltaic performance of the C-PSC. In particular, the maximum PCE of 10.72% has been achieved in the ambient atmosphere, achieving 43% increasing over the pure CC-based device. The improved performance can be attributed to the significant effect of morphological structure of Co-NC(HCl) composite and the synergistic effect of Co-N co-doping on the performance of C-PSCs. Graphical abstract: An efficient Co-NC composite additive for Enhancing Interface performance of carbon-based perovskite solar cells is demonstrated. The champion PCE of the CCo-NC based is boosted from 7.49% to 10.72%, showing an increase by 43%. Image, graphical abstract